Collaboration in Public Service Delivery Promise and Pitfalls - Kekez, Anka; Howlett, Michael; Ramesh, M (Edward Elgar Publishing, 2019)
The growing intensity and complexity of public service has spurred policy reform efforts across the globe, many featuring attempts to promote more collaborative government. Collaboration in Public Service Delivery sheds light on these efforts, analysing and reconceptualising the major types of collaboration in public service delivery through a governance lens. Featuring careful analysis with a global scope, this book unpacks the concept of collaborative service delivery and its practice, drawing from the fields of public policy, public administration, and management. Chapters by leading authors in these areas address service delivery arrangements including co-production, co-management, consultations, contracting-out, commissioning and certification. With a keen focus on conditions that are critical for the success of such collaborative arrangements, as well as their different pathways and pitfalls, the authors suggest ways to improve the analytical, managerial and political capacities needed for successful collaboration in public service delivery. This timely and comprehensive book is useful for students at all levels interested in public policy, governance, administration and management, as well as researchers investigating the governance of collaborative service delivery. Policymakers and practitioners working to re-evaluate and improve public service provision, especially, will also benefit from its insightful discussions of the conditions and mechanisms under which collaborative arrangements operate and fail or succeed.